1975
DOI: 10.1007/978-3-7091-8405-9_17
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of the Chloramphenicol Receptor Site

Abstract: I . I NTRODUCTI ONHaving a relatively simple chemical structure, chloramphenicol became the first antibiotic to be synthesized by organic-chemical methods (Controulis, Rebstock and Crooks, 1949). A large number of chloramphenicol derivatives was subsequently prepared. Kolosov, Shemiakin, Khokhlov and Gurevich tabulated, in 1961, more than 500 such compounds, and the total number of known chloramphenicol derivatives is, by now, much greater.For many of these substances, data on their growth-inhibitory potencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…We tested the effect of CP, which inhibits protein synthesis by inhibiting the peptidyl-transferase activity of the 50s ribosomal subunit (24,25), on the MB-PDA and observed that it did not modify the glucose effect (data not shown). This result suggests that the glucose effect occurs independently of protein synthesis after photodynamic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the effect of CP, which inhibits protein synthesis by inhibiting the peptidyl-transferase activity of the 50s ribosomal subunit (24,25), on the MB-PDA and observed that it did not modify the glucose effect (data not shown). This result suggests that the glucose effect occurs independently of protein synthesis after photodynamic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1): 4-phenylpiperidines (PP); 3,3-diphenylpropylamines (DPA); diamines (DA); and several miscellaneous classes. The problem of deciding whether or not these drugs bind to a unique receptor site remains obscure for both pharmacologists and s P 2 P 3 Douglas et al, 1977Gund and Shen, 1977Gund et al, 1979aSmith et al, 1979Gund and Veber, 1979bLumma et al, 1978Veber et al, 1978Veber, 1980Freidinger and Veber, 1979Hahn and Gund, 1974Stuper et al, 1979Dyott et al, 1980Eaton and Pensak, 1978Nordby and Hodges, 1975 Nordby (to be published) Nordby and Hodges, 1975Cohen, 1979Rohrer et al, 1979Fullerton et al, 1979Fullerton et al. 1980Nichols et al, 1978Marshall et al, 1979Marshall, 1978Gorin and Marshall, 1977Cobb et al, 1978Sufrin et al, 1979Weaver et al, 1979Andrews, 1979bPauling, 1978Cody, 1979Humber et al, 1979Philipp et al, 1979 4 While several uniform receptor models [Feinberg et al, 1976;Galt, 19771 have been proposed, none of them can provide an explanation for the activity encountered in every structural class.…”
Section: A Opiate Receptor Modelingmentioning
confidence: 99%
“…Chloramphenicol (CHL) is a broad-spectrum antibiotic, currently included in List of Essential Medicines (EML) published by the World Health Organization (WHO) [1]. Originally isolated from Streptomyces venezuelae in 1947 [2,3], its structure (shown in Fig. 1) was soon elucidated and became the first antibiotic to be synthesized by chemical means [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Originally isolated from Streptomyces venezuelae in 1947 [2,3], its structure (shown in Fig. 1) was soon elucidated and became the first antibiotic to be synthesized by chemical means [2,3]. CHL acts essentially as a bacteriostatic agent, inhibiting bacterial synthesis by binding to the 50S subunit of 70S ribosomes [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation